Uma breve contextualização dos biossensores eletroquimiluminescêntes voltados para a área clínica e seus princípios - Gomes, Ronewalber Balboena (Universidade Federal de São Carlos, 2024)
Electrochemiluminescence (ECL) emerged in the second half of the 20th century, but was only addressed in the context of biosensors decades later. Research focused on ECL biosensors has gained momentum in recent years with the growing desire to detect pathogens and biomarkers. Most biosensors are still present only in the academic field. In this context, a growing number of biosensors are being developed and reported, new approaches and modifications contribute significantly to the improvement of the device in view of the various analytes involved, such as RNA, DNA, enzymes, proteins or antigens. Therefore, this work briefly explains the general principles that underlie ECL biosensors, the challenges faced and presents some examples of approaches reported in the literature.
A brief description of electrochemiluminescence biosensors, their principles, and applications in clinical analysis
Keywords: Biossensor; Biosensor; Eletrodos descartável; Disposable sensors; Eletroquimiluminescência; Electrochemiluminescence; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::ELETROANALITICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::INSTRUMENTACAO ANALITICA